Proceedings of the 13th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval 1989
DOI: 10.1145/96749.98245
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for dynamic inverted index maintenance

Abstract: For free-text search over rapidly evolving corpora, dy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(58 citation statements)
references
References 4 publications
0
56
0
2
Order By: Relevance
“…When the inmemory index exceeds its limit, it is merged with on-disk index. The simplest form of merge-based update is Immediate Merge, described by Cutting et al [6]. In this approach, only one on-disk inverted index exists.…”
Section: Merge-based Updatementioning
confidence: 99%
See 1 more Smart Citation
“…When the inmemory index exceeds its limit, it is merged with on-disk index. The simplest form of merge-based update is Immediate Merge, described by Cutting et al [6]. In this approach, only one on-disk inverted index exists.…”
Section: Merge-based Updatementioning
confidence: 99%
“…Initially [2,6,16] addressed the problem of on-line indexing. A decade after, Lester et al [14] readdressed the problem and gave a comparative study of three basic approaches: In-place, Re-Merge, and Re-Build, and showed that In-place and Remerge outperform Re-build in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…First, web documents are more dynamic than the text document collections assumed by those techniques. Past work on incremental updates of inverted indexes [3,8,13,27,31] deals mostly with additions of new documents to a collection of static documents. Static documents are existing documents in the collection whose contents do not change over time.…”
Section: Relation With Prior Workmentioning
confidence: 99%
“…The Immediate Merge strategy was first described by Cutting and Pedersen [4]. In their work, they present an index structure based on a B-tree and give a comparison of leave node caching (a form of in-place update) and index remerging.…”
Section: Merge-based Index Maintenancementioning
confidence: 99%